2009
DOI: 10.1016/j.biocon.2008.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Managing natural disturbance in protected areas: Tourists’ attitude towards the bark beetle in a German national park

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 24 publications
4
62
2
1
Order By: Relevance
“…They do not seem to have made their minds either way; perhaps they have received less environmental education than professionals. A similar case was reported by Müller and Job (2009), who wrote that tourists had a neutral attitude towards the bark beetle if they knew little about the species, and a positive attitude if they had a better knowledge about it.…”
Section: Discussionsupporting
confidence: 65%
“…They do not seem to have made their minds either way; perhaps they have received less environmental education than professionals. A similar case was reported by Müller and Job (2009), who wrote that tourists had a neutral attitude towards the bark beetle if they knew little about the species, and a positive attitude if they had a better knowledge about it.…”
Section: Discussionsupporting
confidence: 65%
“…No studies were identified that assess the awareness levels of sea and air passengers relating to tree pests and diseases despite this being identified as an issue (Putulan et al 2004). Müller and Job (2009) explored tourists' attitudes towards the native spruce bark beetle (Ips typographus) in the Bavarian Forest National Park, Germany. The survey in the national park consisted of 608 members of the public identified as tourists (i.e.…”
Section: Outdoor Recreationists and Touristsmentioning
confidence: 99%
“…Attitudes towards conservation have been studied in Yellowstone National Park regarding wolf recovery (Duffield, Neher & Patterson, 2008) and attitudes to bark beetle infestation in a German national park (Müller & Job, 2009). Studies on interrelated attitudes are rarer, but Martín-López, Montes & Benayas (2007) considered biodiversity and its economic value in the Doñana National and Natural Park, Spain.…”
Section: Attitudes To Conservation and Sustainable Development In Parksmentioning
confidence: 99%